Hubungan Antara Stres Dengan Dismenorea Primer Pada Mahasiswi - Ni Nyoman Wahyu Lestarina; Jessica Wahyu Amanda (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Objective: Stress is an adaptive reaction, is very individual so that the stress response of a person with others is not necessarily the same. For a person who experiences a challenging amount of stress, the effect will be different for each person. Too much pressure will cause a person to become stressed. Then came the feeling of excessive worry and feeling very tired. When acute stress increases, this will cause health problems for someone, one of which is dysmenorrhea during menstruation in women. The purpose of this study was to identify the relationship between stress and primary dysmenorrhea in female students.Methods: The research design used in this study is a correlation study with a cross-sectional approach. The variables in this study were stress levels and primary dysmenorrheal pain levels. The measuring instruments used are the Perceived Stress Scale (PSS) and the Numerical Rating Scale (NRS). The samples used were 57 who met the inclusion criteria. The statistical test used in this study is the Spearman Rank (Rho) correlation testResults: The results obtained as many as 84% of female students experienced moderate stress levels, as many as 53% of female students experienced moderate dysmenorrhea pain. The results of statistical tests obtained significance value or Sig. (2-tailed) of 0.612, which means that there is no significant or significant relationship between stress levels and primary dysmenorrheal pain.Conclusion: Many factors can influence women to experience dysmenorrhea. For further researchers are expected to examine other effects of stress on a person.